Criminal Sanctions Against Perpetrators of Underhand Polygamy - Azharuddin, Azharuddin (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2023)
Polygamous marriages are strictly regulated in Indonesia, where the person carrying them out must fulfill very strict conditions, including the permission of the first wife. The difficulty of obtaining permission from the first wife results in frequent underhanded polygamy occurring, the legal consequences of which can sometimes turn to civil law sanctions and also criminal law. This research uses a qualitative research method by describing each data found in concrete terms. The data used is secondary because it is purely a normative discussion, while the legal approach used is a statutory, conceptual and also legal comparative approach. The results of the research show that the provisions of Islamic law justify polygamous marriages on the condition that they are fair. Meanwhile, according to national law, polygamous marriages are basically not permitted, but for Muslims they are permitted with very strict requirements, such as having the permission of the first wife. The absence of permission from the first wife requires men to carry out polygamy under their hands, so that polygamous marriages have implications for civil and criminal sanctions. In civil terms, all the rights of husband and wife are certainly not given to polygamous husband and wife couples, whereas in criminal terms criminal sanctions can be given in the form of imprisonment for five to seven years as regulated in Articles 279 and 280 of the Criminal Code. It is possible that a private polygamous marriage could be included in the legal realm of adultery as regulated in the Criminal Code, considering that the marriage is not recognized by the State, while there is a legitimate wife who feels disadvantaged, because her husband has had sexual relations with another woman Perkawinan poligami telah diatur secara ketat di Negara Indonesia, di mana orang yang melaksanakannya harus memenuhi syarat-syarat yang sangat ketat, di antaranya adalah izin istri pertama. Sulitnya izin istri pertama mengakibatkan sering terjadi poligami di bawah tangan, konsekwensi hukumnya terkadang bisa beralih ke sanksi hukum perdata dan juga hukum pidana. Penelitian ini menggunakan metode penelitian kualitatif dengan cara mendeskripsikan setiap data yang ditemukan secara konkrit, data yang digunakan adalah sekunder karena murni pembahasan secara normatif, sedangkan pendekatan hukum yang digunakan adalah pendekatan perundang-undangan, konseptual dan juga perbandingan hukum. Hasil penelitian menunjukkan bahwa ketentuan hukum Islam, membenarkan perkawinan poligami dengan syarat berlaku adil. Sedangkan dalam ketentuan hukum nasional perkawinan poligami pada dasarnya tidak dibolehkan, namun bagi umat Islam diperbolehkan dengan persyaratan yang sangat ketat seperti harus ada izin istri pertama. Tidak adanya izin istri pertama mengharuskan laki-laki melakukan poligami di bawah tangan, sehingga perkawinan poligami tersebut berimplikasi kepada sanksi keperdataan dan juga pidana. Secara perdata pastinya semua hak-hak suami istri tidak diberikan kepada pasangan suami istri poligami tersebut, sedangkan secara ketentuan pidana bisa diberikan sanksi hukuman pidana berupa penjara selama lima sampai tujuh tahun sebagaimana yang telah diatur dalam Pasal 279 dan 280 KUHP. Dan bisa saja perkawinan poligami di bawah tangan dimasukkan keranah hukum perzinaan sebagaimana yang diatur dalam KUHP, mengingat perkawinan tersebut tidak diakui Negara sedangkan ada istri yang sah merasa dirugikan, karena suaminya telah melakuan hubungan kelamin dengan wanita lain.